Network approach for analyzing and promoting equity in participatory ecohealth research - Mertens, Frederic
Effective involvement and equity in participation between men and women and the various community groups are likely to influence the equity in the sharing of the development outcomes of any participatory research project. The CARUSO project, a participatory research based on the ecosystem approach to human health, showed that the inhabitants from Brasília Legal, a small village located on the river banks of the Tapajós river in the Brazilian Amazon, are exposed to mercury through fish consumption; a subsequent participatory intervention based on dietary changes was effective in reducing mercury exposure of the population. In the present study, we focus on equity in participation and analyze the discussion network about mercury and health to measure individual and group involvement in the community. Participation in the discussion network is associated with the awareness of the critical information necessary to allow the individual to change dietary habits toward the preferential consumption of the less contaminated fish species. Our network analysis shows that gender, age, religion, education, subsistence activities, and spatial distribution of the houses are key elements affecting the involvement of the population in discussions about mercury and health. Based on these results, we propose strategies for integrating the research results and the knowledge of the villagers in a new cycle of participatory research in order to address the lack of involvement of some groups and to promote equitable participation and benefit sharing.
Includes bibiliogaphy.
Keywords: Ecohealth; Ecohealth -- Amazon, Brazil; Fishes; Fishes -- Mercury exposure